"'Worker Center' Found to Be Labor Organization. Issue 2 (13th January 2020) - Unknown
Abstract : The National Labor Relations Act primarily regulates "employers" and "labor organizations." In the past decade or so, a number of alternative employee organizations that claim they are not the type of labor organizations regulated by the NLRA have emerged. These entities have innocuous names such as the "Restaurant Opportunities Center United, " "Working America, " and "National Employment Law Project." These organizations generally represent themselves as employee advocacy groups and disavow any intent of "dealing with employers concerning grievances, labor disputes, wages, rates of pay, hours of employment, or conditions of work, " which is how the National Labor Relations Board defines a labor organization. Not being defined as a "labor organization" under federal labor law has allowed these worker centers to avoid the regulations and restrictions labor law places on the conduct of labor organizations. Under the NLRA, a labor organization is defined as "any organization of any kind, or any agency or employee representation committee or plan, in which employees participate and which exists for the purpose, in whole or in part, of dealing with employers concerning grievances, labor disputes, wages, rates of pay, hours of employment, or conditions of work."